1989
DOI: 10.1111/j.1558-5646.1989.tb04214.x
|View full text |Cite
|
Sign up to set email alerts
|

FILIAL CANNIBALISM IN THE CORTEZ DAMSELFISHSTEGASTES RECTIFRAENUM

Abstract: Abstract.-Male cortez damselfish, Stegastes rectifraenum, in a central Gulf of California population, ate a large percentage (28.3%) ofthe clutches they received. This high rate offilial cannibalism permitted the testing of several predictions concerning the types of clutches that should be preferentially eaten and the mating tactics females should employ to reduce cannibalism rates. Males ate clutches that were smaller than average and that were at early stages of development. Experimentally reduced clutches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As such, large C . spilurus males might benefit from the energy acquired by the complete consumption of the egg clutch laid by a small female and progress to pursuit a larger (more fecund and carrying larger eggs) female [83,84]. The amount of eggs laid by a small female partner might not be enough to compensate the energy expenditures required for the long period of parental care males C .…”
Section: Discussionmentioning
confidence: 99%
“…As such, large C . spilurus males might benefit from the energy acquired by the complete consumption of the egg clutch laid by a small female and progress to pursuit a larger (more fecund and carrying larger eggs) female [83,84]. The amount of eggs laid by a small female partner might not be enough to compensate the energy expenditures required for the long period of parental care males C .…”
Section: Discussionmentioning
confidence: 99%
“…Such behavior can be explained by the presence of eggs directly indicating good parenting skills ( Sargent 1988 ; Kraak and van den Berghe 1992 ), dilution effects ( Ridley and Rechten 1981 ; Unger and Sargent 1988 ), mate choice-copying ( Dugatkin 1992 ; Gibson and Höglund 1992 ; Pruett-Jones 1992 ), increased hatching success with increasing brood size due to lowered filial cannibalism ( Rohwer 1978 ), and expected higher paternal investment in larger and more valuable clutches ( Coleman et al. 1985 ; Sargent 1988 ; Petersen and Marchetti 1989 ; Vallon and Heubel 2017 ). Alternatively, females may prefer males with empty nests or nests that only contain fewer eggs to avoid being the last ( Andrén and Kvarnemo 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, females may prefer males with empty nests or nests that only contain fewer eggs to avoid being the last ( Andrén and Kvarnemo 2014 ). The last added clutch bears the highest risk of filial cannibalism ( Salfert and Moodie 1985 ; Petersen and Marchetti 1989 ; Klug and Lindström 2008 ; Vallon and Heubel 2016 ). This alternative view is especially relevant for common gobies as a species with naturally limited space for eggs in their nest ( Pampoulie et al.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the foraging behavior of female C. sculpturatus exhibiting maternal care may also be caused by a behavioral shift in which females refrain from feeding to decrease the chances of offspring injury or mortality resulting from retaliatory behavior of prey. Further, lessened foraging behavior may improve the chances of offspring survival by reducing the probability of filial cannibalism, when females consume their young to replenish energy invested in reproduction [ 33 , 34 ]. Nevertheless, an earlier study showed that filial cannibalism by brooding female scorpions is a rare occurrence [ 24 ], and indeed we did not observe this behavior in our study.…”
Section: Discussionmentioning
confidence: 99%